The issue of quality of goods: e-consumer protection in Malaysia - Mohd Nor, Roshazlizawati; Amin, Naemah (Journal of Education and Social Science (JESOC), 2015)
E-consumers nowadays are increasingly being involved in online transactions of sale of goods where the purchaser and the vendor are located in different jurisdictions or countries. The communication through web page may or may not carry information as well as details about the supplier and his place of business. The reality is, once the e-consumer has chosen the items of interest, he will proceed to the ‘cash register’ where he will usually be asked to fill in a form and to make payment by credit card or electronic cash. By this, a transaction is concluded and the buyer has performed his duty but the seller’s duty is yet to be performed. As a consumer, one would expect the goods bought to be in good condition and acceptable performance in the manner as advertised or the goods supplied to them have measured up to certain standard of quality. In fact, the rights of consumers with regard to quality of goods or products may be regarded as the very heart of consumer protection law. Thus the problem will arise when the goods sold over the Internet were not fit for the purpose for which they were sold or the quality of goods is not to the expectation of the buyer. Basically, a contract is breached when there is a term in the contract which has not been complied with by either party. The question if the said problems arise are, is there any remedy for the buyer, is it possible to bring an action against the seller and what the e-consumers can do to claim their rights against the supplier or trader. Therefore, this paper discusses the availability of remedies to e-consumer and the challenges to e-consumers in enforcing their rights in cases of breach of contract by e-traders. Adopting a doctrinal study method, the paper evaluates several Malaysian related e-commerce legislation focusing on the protection for e-consumers in this issue namely the Consumer Protection Act 1999, the Sale of Goods Act 1957 and the Contracts Act 1950.